“Place standard” depicts social gradient in the neighbourhood environment in Cyprus - Middleton, Nicos; Kleopa, Daphne; Kouta, Christiana; Kaifa, Stalo; Photiou, Galateia; Panayiotou, Andrie G. (My University, 2020)
Census data, GIS, surveys and audits are used to profile “place”, each with shortcomings. There are several “neighbourhood environment” tools, including the “Place Standard” a policy and advocacy tool developed in Scotland. “Place” is not a strong feature in the public health agenda in Cyprus.
Keywords: Public health; Place Standard; Neighbourhood environment; Censuses; Cyprus; Financial audit; Housing; Internet; Internship and residency; Public health practice; Safety; Scotland; Single parent; Social environment; Socioeconomic factors; Public health medicine; Medical residencies; Construct validity; Advocacy; Agenda; Built environment